Clinical internship in mental health: Deconstruction of prejudice to the stigmatized and construction of care (Research, Society and Development, 2021)
Objective: To report the experience of a nursing student about the deconstruction of prejudice in relation to the stigmatized in the process of mental health care from the clinical practice of graduation. Methodology: Descriptive study, of the experience report type, with data extracted from a 16-day field diary composed of daily reflections, referring to the experience of the nursing student in the practical field of mental health. These reflections were analyzed based on Erving Goffman's theoretical model on stigma and presented in a descriptive way. Results: The student arrived in the practical field with prejudiced beliefs and values towards people with mental health problems, however, with the development of the therapeutic relationship permeated by the bond and trust of both involved, in addition to self-motivation generated with the care, student and together, they were able to deconstruct and reframe their previous conceptions. Final considerations: The experience of insertion in the practical field of mental health, added to the possibilities of the therapeutic relationship, enabled the deconstruction of prejudice by the nursing student towards the stigmatized individual with mental health problems. Furthermore, it can recognize the integrality of the discipline in relation to the nurse's work process.